Supporting troubled young people : a practical guide to helping with mental health problems - Walker, Steven, 1954- (Critical Publishing, 2019)
"'Supporting troubled young people' provides a vital and much-needed resource for those involved with children and young people who are suffering from or at risk of developing, mental health problems. Problems such as self-harm, eating disorders, and anxiety and depression are increasing, while young men, in particular, are at increasing risk of suicide. This is against a backdrop of NHS CAMH services unable to cope with demand and resources in the voluntary sector being stretched beyond their capacity. This means parents, teachers, social workers and nurses are often the first and only help available. This book gives them a jargon-free, accessible guide to help them assess situations, provide skills and guidance to support children and young people, and know how and where to get more help for them"--Publisher's blurb